KEBIJAKAN WALIKOTA BANDA ACEH DALAM MENINGKATKAN PELAYANAN PRIMA BAGI MASYARAKAT DI KOTA BANDA ACEH (Studi Kasus: Pembentukan Mal Pelayanan Publik) - Denny Wias; Ubaidullah, MA; Ardiansyah, MA (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
ABSTRACT,  The success of government agency is reflected by the society satisfaction towards the quality of public services in that agency. It is obvious that people statisfaction is an essential indicator to determine the success of government in providing public services. This research is conducted in Public Service Mall Banda Aceh, Aceh Province. Public Service Mall is a place for the implementation of Public Service which includes goods, services, and administrative service in both licensing and non-licensing. The objectives of this research are: 1). To find out the Banda Aceh Mayor’s Policy in improving Excellent Service for the society of Banda Aceh. 2). To find out the implementation of the Public Service Mall Policy for the society of Banda Aceh. This research used a qualitative research design with descriptive approach. The result showed that Mayor of Banda Aceh policy in improving Excellent Service for the society, proper use of technology, complete of facilities and infrastructure, and etc. In addition, Public Service Mall of Banda Aceh also received full support from Ministry of Administrative and Bureaucratik Reform of the Republic of Indonesia, other regencies in Aceh Province, and Banda Aceh Government. It is proved by available of fund and budget, high quality of electricity and buildings, as well high speed of internet access. Keywords : Policy, Public Service, Public Service Mall